AN ANALYSIS OF THE IMPACT OF JUNK FOOD CONSUMPTION AND EMOTIONAL EATING ON THE RISING TREND OF OBESITY - Nasrin, Razia (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid escalation of obesity across the globe, particularly among adolescents and young adults, has emerged as a critical health crisis in the 21st century. While genetic, metabolic, and sedentary lifestyle factors are frequently acknowledged, recent research increasingly emphasizes behavioral and emotional dimensions—especially the rising prevalence of junk food consumption and emotional eating—as major contributors to the obesity epidemic. This study aims to systematically examine how these two interrelated factors interact and influence the body mass index (BMI), metabolic health, and long-term weight gain. Emotional eating refers to the tendency to consume food often high in sugar, fat, and salt in response to negative emotions such as stress, anxiety, loneliness, or depression, rather than actual physical hunger.1 This behavioral pattern creates a feedback loop wherein unhealthy eating temporarily soothes emotional distress, but subsequently leads to guilt and further emotional eating. Parallelly, junk food—designed to be hyper-palatable and convenient—is widely accessible and heavily marketed, especially to vulnerable populations such as children and urban dwellers. Its addictive qualities, poor nutritional value, and impact on satiety signals in the brain make it a key driver of unhealthy dietary patterns. This research adopts a mixed-methods approach, combining quantitative data from health surveys and BMI records with qualitative insights from interviews and behavioral assessments.2 It aims to establish a correlation between emotional triggers, junk food preferences, and patterns of weight gain. The study also explores socio-cultural influences, media exposure, and psychological vulnerabilities that intensify the reliance on fast food and emotional coping through eating. The findings highlight a pressing need for multidimensional intervention strategies that include nutritional education, mental health support, regulation of junk food advertising, and promotion of mindful eating practices. Addressing emotional well-being and food literacy together is essential to creating sustainable behavioral change and reversing the upward trend of obesity worldwide.